METODE AGILE DEVELOPMENT DALAM PERANCANGAN UNDANGAN DIGITAL MENGGUNAKAN APLIKASI IONIC MOBILE DAN ANGULAR FRAMEWORKS - Ika Kurniawati; Fachri Amsury; Hernawati; Heriyanto (INFOTECH journal, 2024)
Covid-19 pandemic has made people compete to create new digital-based business models, one of which is digital invitations. With the digital invitation, it is expected to reduce waste from paper and plastic produced from conventional invitations in general. In building the application, the author uses the Agile Development Method because this method can provide values faster with better quality and predictions. The Agile Development method in building this application also allows changing needs in the middle of the application Development process, because one of the properties of this method is flexibility. The author uses the Ionic Framework and Elementor in the application Development process because this Framework can produce applications that are easy, fast and have an attractive appearance. We develop this digital invitation application with the hope that people who want to organize events can take advantage of existing technology with digital invitations, instead of using conventional invitations which increase paper and plastic waste. In addition to this, the author's goal in building this application is to create business opportunities, namely by pioneering information technology companies/startups. The results of this study are a Mobile-based digital invitation application that can be downloaded on the Google Play Store which can be used by smartPhone users to create digital invitations